Principles of Macroeconomics - Curtis, Doug; Irvine, Ian (Open textbook library., 2020)
Principles of Macroeconomics is an adaptation of the textbook, Macroeconomics: Theory, Markets, and Policy by D. Curtis and I. Irvine, and presents a complete and concise examination of introductory macroeconomics theory and policy suitable for a first introductory course. Examples are domestic and international in their subject matter and are of the modern era — financial markets, monetary and fiscal policies aimed at inflation and debt control, globalization and the importance of trade flows in economic structure, and concerns about slow growth and the risk of deflation, are included. This textbook is intended for a one-semester course, and can be used in a two-semester sequence with the companion textbook, Principles of Microeconomics. The three introductory chapters are common to both textbooks.